Comparing Microcurrent Therapy Versus Ultrasound Therapy for Subjects with Chronic Temporomandibular Joint Dysfunctions. - V. P., Praison Cherub; Kamalakannan M.; Ramana K.; Anitha A. (Indian Journal of Physiotherapy & Occupational Therapy)
Background: This study was designed to compare the effectiveness of Microcurrent therapy versus Ultrasound therapy in subjects with Chronic Temporomandibular Joint Dysfunctions. Purpose: To compare the effectiveness of Microcurrent therapy versus Ultrasound therapy using the McGill Pain Questionnaire. Materials and Methods: This experimental study has been conducted from November 2022 to April 2023. A total of 24 adults with Chronic Temporomandibular Joint Dysfunctions have been selected using the inclusion and exclusion criteria. They have been split into 2 groups Group A (n=12) and Group B (n=12) were assigned. Group A got Microcurrent therapy, whereas Group B received Ultrasound therapy. The McGill Pain Questionnaire was used to evaluate the subjects. Results: The mean value of Microcurrent therapy at the post-test was found to be higher than the mean value of Ultrasound therapy with a p-value of <0.0001. Conclusion: The result suggests that Microcurrent therapy shows a significant effect in reducing pain in Chronic Temporomandibular Joint Dysfunctions when compared to Ultrasound therapy.